2010
DOI: 10.1016/j.vaccine.2009.12.050
|View full text |Cite|
|
Sign up to set email alerts
|

Age-related efficacy of Shigella O-specific polysaccharide conjugates in 1–4-year-old Israeli children

Abstract: Shigella conjugates are safe and immunogenic in 1-4 years old. The S. sonnei conjugate elicited 71.1% efficacy in the 3-4 years old and can be predicted to be efficacious in individuals older than 3 years of age. These results urge studies with our improved conjugates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
134
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 29 publications
2
134
0
Order By: Relevance
“…A Shigella conjugate vaccine has been shown to elicit significant levels of LPS IgG in children as young as 1 year (52), although this did not translate into protective efficacy for those younger than the age of 3 years (51). We have shown, in the neonatal mouse model, that transcutaneous administration of a neoglycoconjugate vaccine containing a hexasaccharide of V. cholerae OSP was effective in the induction of LPS and vibriocidal antibodies in orally primed mice (44).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A Shigella conjugate vaccine has been shown to elicit significant levels of LPS IgG in children as young as 1 year (52), although this did not translate into protective efficacy for those younger than the age of 3 years (51). We have shown, in the neonatal mouse model, that transcutaneous administration of a neoglycoconjugate vaccine containing a hexasaccharide of V. cholerae OSP was effective in the induction of LPS and vibriocidal antibodies in orally primed mice (44).…”
Section: Discussionmentioning
confidence: 97%
“…OSP-protein conjugate vaccines are under development for a number of diarrheal diseases (49)(50)(51). A Shigella conjugate vaccine has been shown to elicit significant levels of LPS IgG in children as young as 1 year (52), although this did not translate into protective efficacy for those younger than the age of 3 years (51).…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that the S. sonnei conjugate had a protective efficacy of 71 % in 3-4 year-old children, but not in younger ones (Passwell et al, 2010).…”
Section: Inactivated Shigella Vaccine Candidatementioning
confidence: 85%
“…The efficacy of these conjugates was examined where a randomized, double-blind efficacy study was done in 1-4-year-old children at 15 sites throughout Israel (Passwell et al, 2010). The study demonstrated that the S. sonnei conjugate had a protective efficacy of 71 % in 3-4 year-old children, but not in younger ones (Passwell et al, 2010).…”
Section: Inactivated Shigella Vaccine Candidatementioning
confidence: 99%
“…Although, the efficacy for S. flexneri was only 7.9% (95% CI: -153.2-66.5). 22 The main challenge to this vaccine strategy is to provide broad protection against the most common Shigella strains with only one vaccine, as immunogenicity tends to be strain and serotype specific. Given this, synthetic O antigen-derived carbohydrates seem to be promising candidates, first, to reduce the LPS-associated toxicity and second, as a strategy for developing a multivalent conjugate vaccine, which is still required to confer broad protection against different Shigella serotypes (see below).…”
Section: Shigella Sppmentioning
confidence: 99%